The Analysis Of The Relationship Of Total Quality Management (TQM) And Knowledge Management (KM) On The Organisational PerformanCE Of PT. Birawidha Garda Santosa - Eny Kuswidiyanti; Tresna Priyana Soemardi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The challenge of managing security services (Satpam) requires guaranteed service quality in order to increase business sustainability and competitiveness. This study aims to determine the influence of Total Quality Management (TQM) to Knowledge Management (KM) and the influence of TQM to Organizational Performance (KO) and the influence of KM as mediation role between TQM and KO, besides to determine the relationship between sub-dimension TQM and KM in the construct of research relationship model. The desain of this research uses field survey approach (questionnaires). The research sites are in operating areas of PT BGS in Indonesia which spread across 11 provinces of Indonesia with population 1014 security personnels. The sampling number in this study is 144 respondents uses proportional random sampling. Analytical methods used in this study are Structural Equation Model test with the help of SMAT Partial Least Square (SmarPLS) app with the stages measurement model evaluation (validity and reliability), structural model evaluation (to determine strength of the R2 relationship between laten exogen variable), measurement model testing and hypothesis testing. The research results show that TQM has a significant positive effect on KM and KO as shown by p-values of 0.000 and 0.010 respectively. KM also has a significant positive effect on KO as indicated by a p-value of 0.000. KM as a mediating variable has an influence as an enabling factor in achieving organizational performance.